PLANETARY GEAR WITH OFF-CENTROID INNER COGGING IN MECHANICAL ENGINEERING (SURVEY) - Sergey O. Kireyev (Advanced Engineering Research, 2011)
The origination and application history of planetary gearing with the off-centroid inner cogging is considered. Data on their mechanical efficiency, mass-dimensional and inertial characteristics and vibro-activity is presented. A structure model of the most promising design is given.